Effect of Various Parameters on Minimum Mean Square Error and Adaptive Antenna Beamforming using LMS Algorithm - Anjaneyulu, P.; Rao, P.V.D. Somasekhar; Sunehra, Dhiraj (2021 6th International Conference for Convergence in Technology (I2CT), 2021)
Adaptive antennas provide superior system capacities by directing main-beam towards the users of interest while nulling interfering signals. In this paper, effect of various parameters on minimum mean square error and adaptive antenna beamforming is analyzed based on the ability of beam steering and nullifying the interferers. This analysis is carried out by considering Least Mean Square algorithm parameters and antenna parameters such as variation in step-size parameter, variation in signal to interferer ratio and variation in signal to noise ratio. All the parameter variations mainly target effectiveness of beamforming, null depth, convergence speed and mean square error. In all the computed results it has been observed that the LMS algorithm implementation with appropriate antenna input parameters lead to effective nulling at the position of the interferers and minimizing the mean square error.